What is the profilaxy for your costume? (ModaPalavra e-periódico, 2015)
The article investigates the work of the performer ThiagoSoares, or T.Angel, as he is more popularly known. It focuses on the process of creation of performance costumes. Although centered on one artist, the idea is to stimulate reflection on costume processes of the contemporary scene and its diverse variety.
Keywords: costume design; costumes; performance